Ethanol Electrooxidation on Pt with Lanthanum Oxide as Cocatalyst in a DAFC - Santoro, T. A. B.; Neto, A. Oliveira; Forbicini, C. A. L. G. de O.; Linardi, M.; Rodríguez, J. L.; Pastor, E. (International Journal of Electrochemistry, 2012)
Electrocatalytic activity toward ethanol electrooxidation of Pt particles in PtLa/C catalysts with different Pt : La ratios has been studied with different electrochemical and spectroscopic techniques, and the results were compared to those of Pt/C catalyst. Significant enhancement in the electrocatalytic activity has been achieved by depositing the Pt particles with lanthanum oxides/hydroxides using an alcohol reduction method. Compared to Pt/C catalyst, PtLa/C materials exhibit a lower onset potential and a higher electron-transfer rate constant for the investigated reaction. These studies illustrate the possibility of utilizing Pt/C with La oxides/hidroxides as electrocatalyst for direct alcohol fuel cells (DAFCs).